Prevalence of central obesity and associated factors in Ethiopia: A systematic review and meta-analysis - Tegegne, Kirubel Dagnaw; Wagaw, Gebeyaw Biset; Gebeyehu, Natnael Atnafu; Yirdaw, Lehulu Tilahun; Shewangashaw, Nathan Estifanos; Mekonen, Nigusie Abebaw; Kassaw, Mesfin Wudu (Frontiers in Endocrinology, 2022)
Introduction: Obesity is a global public health concern that is now on the rise, especially in low- and middle-income nations. Therefore, this systematic review and meta-analysis aimed to estimate the prevalence of central obesity and its associated factors in Ethiopia. Methods: The online libraries of PubMed, Google Scholar, Scopus, Science Direct, and Addis Ababa University were searched. Data were extracted using Microsoft Excel and analyzed using STATA statistical software (v. 16). Forest plots, Begg's rank test, and Egger's regression test were all used to check for publication bias. To look for heterogeneity, I2 was computed, and an overall estimated analysis was carried out. Subgroup analysis was done by region, and study setting. In addition, the pooled odds ratio for related covariates was calculated. Results: Out of 685 studies assessed, 20 met our criteria and were included in the study. A total of 12,603 people were included in the study. The prevalence of central obesity was estimated to be 37.31 % (95%CI: 29.55–45.07). According to subgroup analysis, the highest prevalence was observed in the Dire Dawa region (61.27%) and community-based studies (41.83%). Being female (AOR=6.93; 95%CI: 3.02-10.85), better socioeconomic class (AOR=5.45; 95%CI: 0.56-10.34), age 55 and above (AOR=5.23; 95% CI: 2.37- 8.09), physically inactivity (AOR= 1.80; 95%CI: 1.37- 2.24), being overweight (AOR=4.00; 95%CI: 2.58-5.41), being obese (AOR=6.82; 95%CI: 2.21-11.43), hypertension (AOR=3.84; 95%CI: 1.29-6.40) were predictors of central obesity. Conclusion The prevalence of central obesity was high in Ethiopia. Being female, having a higher socioeconomic class, being older, being physically inactive, being overweight or obese, and having hypertension were all associated. To reduce the increased prevalence of central obesity, individual factors should be addressed.